Advanced exergy analysis of distillation tower and simulation and optimization by hysys - Darabi, Mohsen; Mohammadiun, Hamid; Mohammadiun, Mohammad (International Journal of Scientific World, 2015)
Exergy rate profiles, exergetic efficiency and irreversibility were used to examine the driving forces in multicomponent distillation system with the view to identifying feasible and efficient operating parameters. The mixture comprised of 5% propane, 15% iso butane, 25% n-butane, 20% iso pentane and 35% n-pentane. Operating variables were feed temperature (-30oC and -80oC), pressure (800KPa and 1200KPa), and reflux-ratio (2 and 6). Sensitivity analysis was carried out to examine the effect of varying operating parameters on the systems. Stage-by-stage system exergy analysis was estimated. Column profiles of a base case -30oC, -80oC, -30oC-reflus ratio 6,80oC -80oC reflux ratio 6 and base case reflux ratio 6 did not cross thus are thermodynamically feasible. Base case -30oC-reflux ratio 2, -80oC-reflux ratio 2, and base case-reflux ratio 2 were crossed and constricted and are infeasible. Base case results gave efficiency of 81.7% at depropanizer and 65.2% at debutanizer. Base cases sensitivity results with -30oC, -80oC and reflux ratio 6, efficiency range 57.40 – 70% and 65.20% - 54.90% for depropanizer and debutanizer respectively. Spitted cases gave 81.7% and 62.20% with more scatter profiles. Splitted feed base case -30oC design gave the lowest overall system exergy loss rate of 1.12E+6 and efficiency of 95.70%.